fMRI and sleep correlates of the age-related impairment in motor memory consolidation - Fogel, Stuart M.; Albouy, Genevieve; Vien, Catherine; Popovicci, Romana; King, Bradley R.; Hoge, Rick; Jbabdi, Saad; Benali, Habib; Karni, Avi; Maquet, Pierre; Carrier, Julie; Doyon, Julien (Human brain mapping, 2014)
Behavioral studies indicate that older adults exhibit normal motor sequence learning (MSL), but paradoxically, show impaired consolidation of the new memory trace. However, the neural and physiological mechanisms underlying this impairment are entirely unknown. Here, we sought to identify, through functional magnetic resonance imaging during MSL and electroencephalographic (EEG) recordings during daytime sleep, the functional correlates and physiological characteristics of this age‐related motor memory deficit. As predicted, older subjects did not exhibit sleep‐dependent gains in performance (i.e., behavioral changes that reflect consolidation) and had reduced sleep spindles compared with young subjects. Brain imaging analyses also revealed that changes in activity across the retention interval in the putamen and related brain regions were associated with sleep spindles. This change in striatal activity was increased in young subjects, but reduced by comparison in older subjects. These findings suggest that the deficit in sleep‐dependent motor memory consolidation in elderly individuals is related to a reduction in sleep spindle oscillations and to an associated decrease of activity in the cortico‐striatal network. Hum Brain Mapp 35:3625–3645, 2014. © 2013 Wiley Periodicals, Inc.